Three Xanthomonas Cell Wall Degrading Enzymes and Sorghum Brown midrib12 Contribute to Virulence and Resistance in the Bacterial Leaf Streak Pathosystem - Qi Wang; Kira M. Veley; Joshua M. B. Johnson; Josh Sumner; Gijs van Erven; Mirjam A. Kabel; Singha Dhungana; Jeffrey Berry; Adam Boyher; David M. Braun; Wilfred Vermerris; Rebecca S. Bart (Molecular Plant-Microbe Interactions)
With an increasing demand for renewable fuels, bioenergy crops are being developed with high sugar content and altered cell walls to improve processing efficiency. These traits may have unintended consequences for plant disease resistance. Xanthomonas vasicola pv. holcicola (Xvh), the causal agent of sorghum bacterial leaf streak, is a widespread bacterial pathogen. Here, we show that Xvh expresses several bacterial cell wall degrading enzymes (CWDEs) during sorghum infection, and these are required for full virulence. In tolerant sorghum, Xvh infection results in the induction of a key enzyme in monolignol biosynthesis, Brown midrib12 (Bmr12), but this did not affect lignin content nor composition. Mutation of Bmr12 rendered the tolerant genotype susceptible. Bmr12 encodes caffeic acid O-methyltransferase (COMT), an enzyme that generates sinapaldehyde as its major product. Growth inhibition of Xvh in the presence of sinapaldehyde was observed in vitro. We conclude that mutations that alter the components of the sorghum cell wall can reduce sorghum resistance to Xvh and that Xvh CWDEs contribute to bacterial virulence. Given the enhanced bioprocessing characteristics of bmr12 sorghum, these results provide a cautionary tale for current and future efforts aimed at developing dedicated bioenergy crops. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.